PERSPEKTIF BANTUAN HUKUM DI KOTA BOGOR DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Roni Ismail; endeh Suhartini (Magister Hukum Sekolah Pascasarjana Unida, 2020)
Legal aid is a constitutional right for Indonesian citizens to obtain legal protection and equality. The existence of Law Number 16 of 2011 is a manifestation of that constitutional right. Fulfillment of legal aid for the poor in Bogor City has been partially implemented using APBD funds in accordance with Regional Regulation No. 3 of 2015 concerning Legal Aid for the Poor and Mayor Regulation Number 39 of 2015 as the Implementing Regulation. The provision of legal aid to the poor in Bogor which refers to the Bogor City Regulation No. 3 of 2015 concerning Legal Aid for the Poor has not yet been realized specifically for the people of Bogor City. This is due to obstacles from external and internal factors in its implementation, namely in the form of a Legal Assistance Organization which is only one accredited at the Ministry of Law and Human Rights and limited funds for absorption of legal aid implementation activities. Therefore, the Government needs to involve Legal Aids (LKBH-LKBH) in private university institutions in Bogor and its surroundings to be able to realize the plan for establishing Legal Consultation innovations (legal clinics) in 68 urban office Bogor City